Penerapan Kompres Jahe Merah untuk Mengurangi Nyeri Osteoarthritis pada Lansia di Wilayah Kerja Puskesmas Pucangsawit - Attyya Putri Azizah; Norman Wijaya Gati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Osteoarthritis often occurs in the elderly aged more than 60 years which is characterized by pain in the joints when moved. In Indonesia, 65% of elderly people aged 60 years and over experience osteoarthritis. Red ginger compress is an alternative nonpharmacological treatment to reduce joint pain in the elderly with osteoarthritis. Objectives: Knowing changes in pain scale in the elderly before and after doing red ginger compresses. Method: This application uses descriptive methods on 2 respondents, with pretest and posttest in the observation sheet of pain scale measuring instruments in the form of NRS (Numeric Rating Scale). Red ginger compress is given 2x a day in the morning and evening for 14 consecutive days within 20 minutes Result: There was a change in the intensity of the pain scale in both respondents. Mrs. P from moderate scale to mild scale and Mrs. E from moderate scale to painless scale. Conclusion: The application shows that there are changes in the pain scale before and after the red ginger compress, both in the first respondent and the second respondent. Red ginger compress can reduce osteoarthritis joint pain in the elderly.